Intonational Cues to Segmental Contrasts in the Native Language Facilitate the Processing of Intonational Cues to Lexical Stress in the Second Language - Kim, Hyoju; Tremblay, Annie (Frontiers in Communication, 2022)
This study examines whether second language (L2) learners’ processing of an intonationally cued lexical contrast is facilitated when intonational cues signal a segmental contrast in the native language (L1). It does so by investigating Seoul Korean and French listeners’ processing of intonationally cued lexical-stress contrasts in English. Neither Seoul Korean nor French has lexical stress; instead, the two languages have similar intonational systems where prominence is realized at the level of the Accentual Phrase. A critical difference between the two systems is that French has only one tonal pattern underlying the realization of the Accentual Phrase, whereas Korean has two underlying tonal patterns that depend on the laryngeal feature of the phrase-initial segment. The L and H tonal cues thus serve to distinguish segments at the lexical level in Korean but not in French; Seoul Korean listeners are thus hypothesized to outperform French listeners when processing English lexical stress realized only with (only) tonal cues (H* on the stressed syllable). Seoul Korean and French listeners completed a sequence-recall task with four-item sequences of English words that differed in intonationally cued lexical stress (experimental condition) or in word-initial segment (control condition). The results showed higher accuracy for Seoul Korean listeners than for French listeners only when processing English lexical stress, suggesting that the processing of an intonationally cued lexical contrast in the L2 is facilitated when intonational cues signal a segmental contrast in the L1. These results are interpreted within the scope of the cue-based transfer approach to L2 prosodic processing.